THE BEHAVIOR OF COASTAL COMMUNITIES ON WASTE MANAGEMENT IN UNTIA FISHERMAN VILLAGE, MAKASSAR - Rifahmi, Rifahmi; Sukimin, Ridwan; Polapa, Funty (Hasanuddin University, 2023)
Waste has now become a global issue, with Indonesia being the world's second greatest producer. The presence of waste that ends up in the water imposes additional responsibilities on those who reside in coastal areas to limit the presence of waste. The purpose of this research is to determine community behavior in garbage processing, particularly in coastal towns. The methods employed are observation, interviews, and surveys, all of which are interconnected and should yield the most data. To validate the data, an analysis was performed using the SPSS instrument. In this study, 17 household, with the results indicating that the community's understanding of garbage and its many categories was extremely good (65%). This is aided by community understanding in trash management, as well as community awareness and readily available support facilities.